Perbedaan Perilaku Agresif antara Siswa Aktif dengan Tidak Aktif dalam Kegiatan Ekstrakurikuler di SMPN 3 Way Jepara - Mudaim Mudaim; Eko Susanto (Indonesian Journal of Educational Counseling, 2019)
DIFFERENCES IN AGGRESSIVE BEHAVIOR BETWEEN ACTIVE STUDENTS AND INACTIVE IN EXTRACURRICULAR ACTIVITIES AT JUNIOR HIGH SCHOOL 3 OF WAY JEPARA. Aggressive behavior in adolescence is often shown with courageous attitude against parents and teachers, mischief, crime and acts aggressively. This study will look at differences in aggressive behavior between active and inactive students in extracurricular activities in Junior high School 3 of Way Jepara. The method of this study is comparative research, where the instrument that used for collecting the data is scale of aggressive behavior. The population of this research is eighth and ninth grade students of Junior High School 3 of Way Jepara in East Lampung that consist of 180 students. The sample is took by Disproportionate Stratified random Sampling, then it is obtained the sample of 124 of active extra-curricular students, whereas, the non-active extra-curricular student that consist 56. Hypotheses assessment is conducted by independent sample t-test where obtain calculated value of aggressive behavior in 1.360 with significance level of 0.015. Because p < 0.05 so Ho refused. There are some differences between active students and inactive students of extra-curricular.